Biosynthesis of Multicomponent Nanoparticles with Extract of Mortiño (Vaccinium floribundum Kunth) Berry: Application on Heavy Metals Removal from Water and Immobilization in Soils - Mayra Abril; Hugo Ruiz; Luis H. Cumbal (Journal of Nanotechnology)
Through preparation of multicomponent nanoparticles (MCNPs) using ferric chloride (FeCl3), sodium sulfate (Na2SO4), and the extract of mortiño fruit (Vaccinium floribundum Kunth), we dramatically improved the removal/immobilization of heavy metals from water and in soils. As-prepared nanoparticles were spherical measuring approximately 12 nm in diameter and contained iron oxides and iron sulfides in the crystal structure. Removal of copper and zinc from water using MCNPs showed high efficiencies (>99%) at pH above 6 and a ratio of 0.5 mL of the extract:10 mL 0.5 M FeCl3·6H2O : 10 mL 0.035 M Na2SO4. The physisorption process followed by chemisorption was regarded as the removal mechanism of Cu and Zn from water. While, when MCNPs were used to treat soils contaminated with heavy metals, more than 95% of immobilization was accomplished for all metals. Nevertheless, the distribution of the metallic elements changed in the soil fractions after treatment. Results indicate that immobilization of metals after the injection of nanoparticles into soils was effective. Metals did not leach out when soils were drained with rain, drinking, and deionized water but fairly leached out under acidic water drainage.